Exploring a COVID‐19 Endemic Scenario: High‐Resolution Agent‐Based Modeling of Multiple Variants. Issue 1 (11th November 2022) - Truszkowska, Agnieszka; Zino, Lorenzo; Butail, Sachit; Caroppo, Emanuele; Jiang, Zhong‐Ping; Rizzo, Alessandro; Porfiri, Maurizio
Abstract: Our efforts as a society to combat the ongoing COVID‐19 pandemic are continuously challenged by the emergence of new variants. These variants can be more infectious than existing strains and many of them are also more resistant to available vaccines. The appearance of these new variants cause new surges of infections, exacerbated by infrastructural difficulties, such as shortages of medical personnel or test kits. In this work, a high‐resolution computational framework for modeling the simultaneous spread of two COVID‐19 variants: a widely spread base variant and a new one, is established. The computational framework consists of a detailed database of a representative U.S. town and a high‐resolution agent‐based model that uses the Omicron variant as the base variant and offers flexibility in the incorporation of new variants. The results suggest that the spread of new variants can be contained with highly efficacious tests and mild loss of vaccine protection. However, the aggressiveness of the ongoing Omicron variant and the current waning vaccine immunity point to an endemic phase of COVID‐19, in which multiple variants will coexist and residents continue to suffer from infections. Abstract : Mathematical models have arisen as powerful tools in the worldwide fight against COVID‐19. This paper establishes a high‐resolution computational framework for modeling the simultaneous spread of two variants in a medium‐size U.S. town. The model is used to study how tests and vaccines can effectively curb new COVID‐19 waves and help in the preparation for the next phases of this pandemic.